Slovenski začetki medicine dela v Idriji v 18. stoletju - Zupanič Slavec, Zvonka (Medicinski razgledi, 1996)
Of all medical sciences in Slovenia, occupational medicine has one of the longest traditions. It is not a mere coincidence that began to develop in Idrija as early as the beginning of the 18th century. The Idria mercury mine,the second largest mine of the world after Almaden in Spain, was owned bythe Habsburg dinasty for four centuries. The working atly reduced by chronicpoisoning with mercury, and in order to attain higher production of themine, medical and social care for miners was provided in Idria much earlierthan anywhere else. The first, and one of the most prominent doctors inIdria, dr. J. A. Scopoli described in exhaustive detail the symptoms of chronic intoxication with mercury in his work De Hydrargyro Idriensi TentaminaPhysico-Chymico-Medica and thus took his place among the pioneer authors of works on occupational medicine, hygiene and toxycology. His predeceeders were Ellenbog, Paracelsus, Mattioli and some others. The paper describes the situation in the Idria mine in the 17th and 18th century, focusing on the Scopoli's mineralogical and medical discussion on mercury miners and mercurialism.
Keywords: medicina dela; zgodovina; history; Idrija